ANALISIS IMPROVISASI ALTO SAXOPHONE PADA LAGU PERFUME DE GARDENIAS YANG DIMAINKAN OLEH MIGUEL ZENON - Anggi Surya Nugraha Harahap (Saraswati)
Music has many genre and will continue to evolve over the course of human life. This paper will discuss the result of improvisation in jazz music. Improvisation is in ‘the heart’ of jazz music. Listening jazz music not only the ears but also with fellings. Miguel Zenon is a composer, arranger and saxophonist a famous scene in the jazz world. Perfume De Gardenias entrance in the album Alma Adentro : The Puerto Rican Song Book. Perfume De Gardenias is the result arrangement Miguel Zenon, original song created by a composer from Puerto Rico, Rafael Hernandez. This song researched by qualitative methods, has a lot of analysis original song form Perfume De Gardenias, analysis form and performing alto saxophone Miguel Zenon which has been arranged and analysis improvisation alto saxophone.The analysis was conducted on the song form and improvisation approach. The result of this study is improvisation alto saxophone Miguel Zenon are rarely encountered in a general jazz song, which became the typical Miguel Zenon.   Keywords : Analysis, improvisation, alto saxophone, Miguel Zenon, Perfume De Gardenias.